Programmable Multiplexed Nucleic Acid Detection by Harnessing Specificity Defect of CRISPR‐Cas12a - Xin Guan; Rui Yang; Jiongyu Zhang; Jeong Moon; Chengyu Hou; Chong Guo; Lori Avery; Danielle Scarola; Daniel S. Roberts; Rocco LaSala; Changchun Liu (Advanced Science)
Abstract CRISPR‐Cas12a works like a sophisticated algorithm in nucleic acid detection, yet its challenge lies in sometimes failing to distinguish targets with mismatches due to its specificity limitations. Here, the mismatch profiles, including the quantity, location, and type of mismatches in the CRISPR‐Cas12a reaction, are investigated and its various tolerances to mismatches are discovered. By harnessing the specificity defect of the CRISPR‐Cas12a enzyme, a dual‐mode detection strategy is designed, which includes approximate matching and precise querying of target sequences and develop a programmable multiplexed nucleic acid assay. With the assay, 14 high‐risk human papillomavirus (HPV) subtypes are simultaneously detected, collectively responsible for 99% of cervical cancer cases, with attomolar sensitivity. Specifically, the assay not only distinguishes HPV16 and HPV18, the two most common subtypes but also detects 12 other high‐risk pooled HPV subtypes. To enable low‐cost point‐of‐care testing, the assay is incorporated into a paper‐based microfluidic chip. Furthermore, the clinical performance of the paper‐based microfluidic chip is validated by testing 75 clinical swab samples, achieving performance comparable to that of PCR. This programmable multiplexed nucleic acid assay has the potential to be widely applied for sensitive, specific, and simultaneous detection of different pathogens.